Organizing Teaching around the Cycle System (Praxis Educativa, 2012)
The organization of teaching in our country adopted the so-called cycle system as a result of the Federal Act of Education 24195/1992, cycles, which have lost (or various reasons their pedagogical sense. Especially in the third cycle, the importance of spatial, temporal, physical and mental rites of passage for learners' emotional, intellectual and social maturing process has been disregarded. This work aims at providing some answers lo this problem, based on personal reflection and experience shared with other colleagues, what does not preclude other responses as valid as ours It certainly would be beneficial for the educational system as a whole, to submit this topic to a rigorous and honest pedagogical debate in order to signal points of agreement and disagreement Each culture turns Us rites of passage or initiation into a dilemma or a celebration. On the grounds of our cultural and institutional history, we should not be ashamed of walking some steps backward to recover and improve.
Keywords: educational reform; cycle system; maturing; learner; culture